Agonistic and antagonistic targeting of immune checkpoint molecules differentially regulate osteoclastogenesis - Brom, Victoria C.; Strauss, Andreas C.; Sieberath, Alexander; Salber, Jochen; Burger, Christof; Wirtz, Dieter C.; Schildberg, Frank A. (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors are used in the treatment of various cancers and have been extensively researched with regard to inflammatory and autoimmune diseases. However, this revolutionary therapeutic strategy often provokes critical auto-inflammatory adverse events, such as inflammatory reactions affecting the cardiovascular, gastrointestinal, nervous, and skeletal systems. Because the function of these immunomodulatory co-receptors is highly cell-type specific and the role of macrophages as osteoclast precursors is widely published, we aimed to analyze the effect of immune checkpoint inhibitors on these bone-resorbing cells. We established an in vitro model of osteoclastogenesis using human peripheral blood mononuclear cells, to which various immune checkpoints and corresponding antagonistic antibodies were administered. Formation of osteoclasts was quantified and cell morphology was analyzed via immunofluorescence staining, cell size measurements, and calculation of cell numbers in a multitude of samples. These methodical approaches for osteoclast research achieved objective, comparable, and reproducible results despite the great heterogeneity in the form, size, and number of osteoclasts. In addition to the standardization of experimental analyses involving osteoclasts, our study has revealed the substantial effects of agonistic and antagonistic checkpoint modulation on osteoclastogenesis, confirming the importance of immune checkpoints in bone homeostasis. Our work will enable more robust and reproducible investigations into the use of immune checkpoint inhibitors in conditions with diminished bone density such as osteoporosis, aseptic loosening of endoprostheses, cancer, as well as the side effects of cancer therapy, and might even pave the way for novel individualized diagnostic and therapeutic strategies.